Republic of Slovenia : Staff Report for the 2013 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2014)
This Information Annex highlights that Slovenia maintains an exchange system that is free of restrictions on the making of payments and transfers for current international transactions, with the exception of exchange restrictions maintained for security reasons. Slovenian fiscal statistics are timely and high quality. The Ministry of Finance publishes a comprehensive monthly Bulletin of Government Finance, which presents monthly data on the operations of the state budget, local governments, social security, and the consolidated general government. The coverage of general government excludes the operations of extrabudgetary funds and general government agencies' own revenues. However, these operations are small.